“Simply Math”—A Hybrid MOOC Supporting Advanced Mathematics Learning in Israeli Secondary Schools - Halima Sharkia; Zehavit Kohen (Education Sciences)
The present study explores the integration of a hybrid MOOC (H-MOOC) called Simply Math in the setting of advanced mathematics lessons in school. Considering two components—institutional support and curricular content alignment—the H-MOOC theoretical framework was applied to this study to gain a better understanding of how existing MOOCs can be incorporated into the secondary school curriculum. This understanding was informed by examining the perceptions of 55 high school teachers of the use of H-MOOC, and through two case studies of teachers Raya and Israa, who integrated the H-MOOC into their mathematics lessons. The research tools included a perception questionnaire, as well as classroom observations and retrospective interviews. The findings revealed that the two components illustrating the implementation of the H-MOOC were highly evident in the current study. Specifically, concerning the institutional goals, numerous key components and attributes of hybrid learning were identified in practice, indicating successful MOOC implementation. The H-MOOC’s value stood out in promoting active learning, fostering interaction between the teacher and students, intensive problem-solving, and collaborative group learning. With respect to the curricular content alignment, higher satisfaction was observed with the online filmed lectures than with the online exercises.